Institutionalist perspectives on international policy coordination in Asia: the case of NCD prevention policy. Issue 1 (2nd January 2018) - Kay, Adrian
ABSTRACT: This paper argues that there is greater international policy coordination capacity in Asia than commonly acknowledged in claims about strong mutual assertions and recognition of national sovereignty. The paper dissects the notion of 'weak institutions' at the international level by developing conceptually an argument about relationships between formal and informal institutions. The argument is then illustrated by cases drawn from public health policy coordination in Asia. A brief concluding section highlights the relationship between formal and informal institutions as critical to investigations of the strength of different modes of international policy coordination in Asia.